Limb Salvage and Reconstruction of a Complex Upper Extremity Injury: A Case Report - Christos Koukos; Mikail Chatzivasiliadis; Stylianos Kapetanakis; David Latz; S Samundeeswari; Fredy Montoya (Journal of Orthopaedic Case Reports)
Introduction: Complex upper extremity trauma poses us with significant challenges in orthopedic and reconstructive surgery due to the complex anatomy and functional importance of the extremities. These injuries are often the result of high-energy mechanisms like motor vehicle collisions, which makes their management particularly demanding. Making the decision between limb salvage and amputation in such cases requires careful consideration of multiple factors such as functionality, risk of complications, and recovery. Case Report: We describe the case of a 39-year-old male who had sustained an open fracture of the elbow, avascular necrosis of the olecranon, a displaced ulna fracture, and transections of the triceps tendon and ulnar nerve. We tried to salvage the limb through planned reconstructive surgeries despite the complexity of the injuries and recommendations for amputation. Conclusion: Managing complex upper extremity trauma requires a structured approach that balances innovative techniques with effective infection control and soft-tissue reconstruction.